Migration in EU: Impication to the Regional Integration - Indraswari, Ratih (Parahyangan Center for International Studies, 2014)
The paper aims to address the imigrations issues in European Union (EU) and its relation to the continuation of closer union. Migrations becomes essential, yet delicate issues on the integration of Europe based on the socio-economic impacts they create. Two importants relations will be focused on, first is the relations between migration the problems of aging population and second is the realtion between migration and social tension. This paper concludes that the negative excess of economic achievement on socio-culture will potentially hamper the regional integration.